2017
DOI: 10.21542/gcsp.2017.9
|View full text |Cite
|
Sign up to set email alerts
|

Hydatid cyst of the interventricular septum

Abstract: While cardiac involvement is not a common presentation in human echinococcosis, it may lead to life-threatening complications including cyst rupture; anaphylactic shock; tamponade; pulmonary, cerebral or peripheral arterial embolism; acute coronary syndrome; dysrhythmias; infection; ventricular or valvular dysfunction, as well as sudden death. Here we report a 9-year old girl who was diagnosed to have hydatid cyst of the interventricular septum four years after diagnosis and medical treatment of pulmonary hyda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
(5 reference statements)
0
13
0
Order By: Relevance
“…5 Cardiac symptoms range from space-occupying effects causing low cardiac output states, heart failure or valvular dysfunction. 9 Invasion and irritation of the conduction pathways lead to dysrhythmias, palpitations, syncope or sudden death. 9 Hydatid cysts can rupture causing pericardial tamponade, pericarditis or systemic dissemination of antigenic material with life-threatening anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 Cardiac symptoms range from space-occupying effects causing low cardiac output states, heart failure or valvular dysfunction. 9 Invasion and irritation of the conduction pathways lead to dysrhythmias, palpitations, syncope or sudden death. 9 Hydatid cysts can rupture causing pericardial tamponade, pericarditis or systemic dissemination of antigenic material with life-threatening anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Invasion and irritation of the conduction pathways lead to dysrhythmias, palpitations, syncope or sudden death. 9 Hydatid cysts can rupture causing pericardial tamponade, pericarditis or systemic dissemination of antigenic material with life-threatening anaphylaxis. 2 , 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through careful consideration, the family refused surgical treatment due to high risk of the procedure and asked to be discharged without any further treatment. Tefera et al [26] reported a case with a large hydatic cyst within the interventricular septum in a 9-year-old girl, who underwent surgery under cardiopulmonary bypass. There was no cyst in other organs or tissues.…”
Section: Discussionmentioning
confidence: 99%